Acquired Elliptocytosis as a Manifestation of Myelodysplastic Syndrome with Ring Sideroblasts and Multilineage Dysplasia - Kjelland, Jacob D.; Dwyre, Denis M.; Jonas, Brian A. (Case Reports in Hematology, 2017)
Acquired elliptocytosis is a known but rarely described abnormality in the myelodysplastic syndromes (MDS). Here we report the case of an elderly male who was admitted to the hospital with chest pain, dyspnea, and fatigue and was found to be anemic with an elliptocytosis that had only recently been noted on peripheral smears of his blood. After bone marrow biopsy he was diagnosed with MDS with ring sideroblasts and multilineage dysplasia and acquired elliptocytosis. Here we report a rare case of acquired elliptocytosis cooccurring with MDS with ring sideroblasts and multilineage dysplasia.